Dissecting the Role of the FGF19-FGFR4 Signaling Pathway in Cancer Development and Progression - Liu, Yanan; Cao, Meng; Cai, Yuepiao; Li, Xiaokun; Zhao, Chengguang; Cui, Ri (Frontiers in Cell and Developmental Biology, 2020)
Fibroblast growth factor (FGF) receptor 4 (FGFR4) belongs to a family of tyrosine kinase receptor. FGFR4 is highly activated in certain types of cancer and its activation is closely associated with its specific ligand, FGF19. Indeed, FGF19-FGFR4 signaling is implicated in many cellular processes including cell proliferation, migration, metabolism, and differentiation. Since active FGF19-FGFR4 signaling acts as an oncogenic pathway in certain types of cancer, the development and therapeutic evaluation of FGFR4-specific inhibitors in cancer patients is a topic of significant interest. In this review, we aim to provide an updated overview of currently-available FGFR4 inhibitors and their ongoing clinical trials, as well as upcoming potential therapeutics. Further, we examined the possibility of enhancing the therapeutic efficiency of FGFR4 inhibitors in cancer patients. We also discussed the underlying molecular mechanisms of oncogenic activation of FGFR4 by FGF19.